Design of an integrated body motion training platform - Go, Tiong Sen (2015)
Wearable technology has become a hot topic within the ‘tech’ world in the recent years. Wearable is wearing a computer on the body that normally contains sensors and feedback systems for the user. Therefore, this opened up possibilities in all sorts of technological fields for wearable technologies. One of the most common feedback systems is the vibrotactile feedback. It can send discrete messages to user by varying the intensity, frequency or location of vibration. This project investigates the location, frequency and pattern for the tactors with a self-made vibrotactile device. In particular, the main focus involves the development of two vibrotactile devices, one with two tactors configuration, while the other is a six tactors configuration. The intention was to improve on the design of the previous FYP student. Three experiments were conducted to investigate on the frequency, pattern and time duration of vibration. The results obtained show that skin has better reception to lower frequency, short burst of vibration and a spacing of 40mm between tactors. These results were then used to develop the two vibrotactile devices. The prototype was made to have a better durability with the use of existing sports wristguard. On top of that, the box was designed to be user friendly, it has a control box with removable lid, battery operated instead of Li-Po battery due to easy replacement, and lastly it has the capability to be reprogrammed easily. The prototypes could be used for many applications such as, a rehabilitation device similar to the previous FYP, a communication device, further study the different haptic patterns that could be employed. There are several suggestions for future works. Firstly, the accuracy of vibrotactile feedback could be further improved. Secondly, different tactile feedback could be studied to compare their accuracy and applications. Lastly, the device could be further improved by making it more compact and aesthetically pleasing.